Adaptive Leadership In Islamic Education Management To Face Challenges In The Digital Era - Umu Hani; Selnistia Hidayani (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
This study examines an Ronald Heifetz adaptive leadership in the context of Islamic education management in the digital era. Rapid advances in information technology have transformed educational institutions to adapt continuously while preserving fundamental Islamic values. This research applies a qualitative method using a library research approach to find out the role of adaptive leadership in Islamic education management and the Islamic values that reinforce this leadership practice in the digital era by reviewing and analyzing relevant journals, articles, and academic books. The findings demonstrate that adaptive leadership is essential for responding to digitalization challenges because it highlights leaders’ capacity for critical thinking, innovation, flexibility, and effective decision making. Islamic values such as Amanah, adl, shura, shiddiq, fathanah, and tabligh function as ethical foundations that reinforce adaptive leadership practices. These values not only enhance managerial effectiveness within educational institutions to balance technological advancement with religious principles, but also help them remain resilient in the rapidly changing educational environment in contemporary society.